BSR Spondyloarthritis Course, 27 February 2020. Spondyloarthritis: pathogenesis, diagnosis and management. Issue 2 (1st September 2020) - Marzo-Ortega, Helena; Tan, Ai Lyn; McGonagle, Dennis; Pickles, David; Dubash, Sayam; Vandevelde, Claire Y; Coates, Laura C; Siebert, Stefan; Helliwell, Philip S
Abstract: High-quality continuous medical education is essential to maintain excellence in health-care delivery, upskilling professionals and improving patient outcomes. This is particularly relevant when addressing rare disease groups, such as the spondyloarthritides, a group of heterogeneous inflammatory conditions that affect joints and other organs, such as the skin, bowel and eye. Professional bodies, such as the British Society for Rheumatology (BSR), are well placed to deliver this type of education. In 2020, the BSR ran a dedicated SpA course aimed at rheumatology health- care professionals wishing to update their basic knowledge of SpA with a review of the latest advances in the field. Here, we summarize the proceedings of the meeting and discuss the value of such an initiative.